A simple design of water-based broadband metamaterial absorber for THz applications - Nguyen, Thi Kim Thu\(^{1,2}\); Nguyen, Thi Minh; Nguyen, Hong Quang; Nguyen, Thi Minh Tam; Ho, Thi Huyen Thuong; Pham Tra, My; Vu, Dinh Lam; Nguyen Thi Quynh, Hoa (Communications in Physics, 2023)
A simple water-based broadband metamaterial absorber has been proposed for the terahertz region. The absorption bandwidth is extended based on large frequency dispersive permittivity and high relative dielectric loss of water. The simulated result indicates that the absorption of the proposed structure achieves over 90% in the frequency range from 0.6 to 10 THz at a normal incident angle. Moreover, the performance maintains high over 80% with a wide incident angle up to 60o for transverse electronic (TE) mode and over 90% up to 700 transverse magnetic (TM) mode in the entire operating frequency range. Therefore, the designed absorber has a potential candidate for broadband THz applications.